ANALISIS KOMODITAS BASIS SUB SEKTOR TANAMAN PANGAN DI KECAMATAN BUKO SELATAN KABUPATEN BANGGAI KEPULAUAN - Hardin Hamsir; Hadayani Hadayani; Arifuddin Lamusa (Agroland: Jurnal Ilmu-ilmu Pertanian, 2019)
The purposes of this study were to identifying basis and non basis commodities in food crop sub-sectors in South Buko sub-district; to identifying changes in the role of basis and non basis commodities in food crop sub-sectors in South Buko sub-district; and to identifying the growth and competitiveness of commodities in food crop sub-sector in South Buko District. Data were analyzed using Location Quotient, Dynamic Location Quotient and Shift Share analysis. There were two types of basis commodities i.e. peanuts and sweet potatoes with an average LQ values of 2.64 and 1.01, respectively. Similarly, the two commodities were also expected to be the basis commodities for the future with the average values of DLQ were 4.59 and 1.40, respectively.  The combined analysis of Location Quotient and Dynamic Location Quotient shows that both commodities will remain the basis crops for the present and the future whereas corn and cassava will remain non-basis commodities. The proportional growth of all food crops sub-sector commodities are positive as well as the regional share growth of corn. On the contrary peanuts, cassava and sweet potatoes are negative.